Human Capital Development, Healthcare Financing and Institutional Quality in Nigeria - Pocho, Anthony Gabriel; Matudi, Inusa Utiwore (Cattleya Darmaya Fortuna, 2026)
Human capital development, healthcare financing and institutional quality are key variables that affect the growth of the economy, especially for a developing economy which Nigeria belongs to. This study interrogates the nexus between human capital development, healthcare financing and institutional quality in Nigeria between 1996 to 2023. Using the Auto Regressive Distributed Lag (ARDL) model approach. Outcome indicated that; futuristically, educational expenditure exhibited positive and significant effect on institutional quality index in Nigeria. Additionally, healthcare expenditure exhibited negative and significant effect on institutional quality in Nigeria. And out of pocket expenditure showed negative and insignificant effect on institutional quality in Nigeria. However, in the short run, outcome indicated that, healthcare expenditure exhibited negative and significant effect on institutional quality in the short run, on the other hand, out of pocket expenditure showed to have positive and insignificant effect on institutional quality index. On this premise, the study suggested that concern authorities should revisit Nigeria’s healthcare financing model, strive to enhance budgetary allocation to the educational and health sector this might improve the quality of human capital and improve the aggregate health of the citizens. Nigeria needs strong institutions to manage funds allocated to the educational and health sector effectively.